An Analytical Study of Standard Pashto Language - Omarkhel , Hameedullah; Tasal, Mohhamad Qasim (Integrated Journal for Research in Arts and Humanities, 2024)
Linguistics has different branches; the most famous branch is called descriptive linguistics. Linguistics is an excellent branch of descriptive linguistics and it is a science that studies the sub-systems of a comprehensive system of a language. As you can see, every language has its own dialects, like other languages, Pashto has many dialects due to the presence of speakers in different regions. Dialect is a style of communication or a type of speech. Dialect in English is called dialect, which is made from the Greek word (dialectos and dialectos means the way of speaking. The issue of standard language is a matter of cultural and social popularity, and all social popularity has economic and political roots. Standard dialect is called standard dialect in English; Therefore, if all dialects of a language are eliminated, one dialect is considered the standard dialect to be used, selected and accepted for speaking and daily writing in terms of social, tabriz, cultural and political status is called standard dialect. Pashto may have unity to some extent, but dialectic unity is less. In Kabul, some pen holders and a certain amount of official power holders mention the standard language, which has no oral existence, but only a written form; So, on this basis, one can say that until now, there is no public oral standard language understood in Pashtuns, which has become popular among the people from the point of view of its social popularity. In this writing we become familiar with other idioms beside standard dialect.